(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2020)
A mind as privileged as that of the Joaquin Costa Aragonese polygraph who, the same went through history, literature, geography, pedagogy, anthropology, agriculture, economics, politics or law, could glimpse the interrelation between the different disciplines of knowledge. Costa, ahead of his time once again, connects the law and the economy to warn of the possible conflict between justice and utility. Nowadays, thanks to the presence of the economic analysis of law (AED), this conflict is still alive under the terms of the efficiency-equity binomial, and stands as one of the keys to explaining and designing law through an economic perspective, faced with the challenge of satisfying a wide range of needs within the framework of limited resources, which must be managed and dosed appropriately. Costa’s merit in this matter lies, on the one hand, in having detected this point of friction as the basis of the problems suffered in Spain at the time; and, on the other, to succeed in proposing the regeneration of the lost balance through justice, in a society frequently guided by a misunderstood principle of utility.